PENGARUH AUDIT INTERNAL DAN GOOD CORPORATE GOVERNANCE TERHADAP PENCEGAHAN FRAUD - Putri, Amanda; Aulia, Amanda; Muslim, Ade (Fakultas Ekonomi dan Bisnis Universitas Pasundan, 2025)
This study aims to analyze the influence of Internal Audit and Good Corporate Governance (GCG) on fraud prevention in insurance companies listed on the Indonesia Stock Exchange in 2022–2023. Using secondary data from annual reports and financial statements, a quantitative descriptive approach with multiple linear regression was used as the research methodology. The results indicate that, partially, Internal Audit has no significant effect on fraud prevention, while GCG has a significant effect. However, simultaneous test results indicate that Internal Audit and GCG together have a significant effect on fraud prevention. This indicates that the effectiveness of fraud prevention in the insurance sector will be optimal if the implementation of internal audit is integrated with good corporate governance. This study implies that insurance companies need to strengthen the synergy between the internal audit function and GCG implementation to minimize the risk of fraud that can harm the company.